Cronkhite–Canada syndrome: An investigation in clinical features and pathogenesis - Zhu, Lan Ping; Zhong, Wei Long; Wang, Ze Gui; Sun, Kai Di; Liu, Qin Ling Fei; Zhao, Jing; Zhao, Jing Wen; Chen, Xin; Wang, Bang Mao (Journal of digestive diseases, 2021)
Objective This study aimed to investigate the clinical features and potential pathogenesis of a rare nonhereditary polyposis syndrome, Cronkhite–Canada syndrome (CCS). Methods Medical records of eight patients with CCS who were admitted to our hospital from January 2005 to November 2019 were reviewed. Transcriptome profiling was performed in one patient to investigate its difference between gastric polyp tissue and normal mucosa. Differentially expressed genes (DEGs) were determined for functional analysis. The expression of inhibin beta A (INHBA) was further assessed by using immunohistochemistry. Results All patients presented with gastrointestinal polyposis, accompanied by diarrhea, skin hyperpigmentation, hair loss and nail dystrophy. Hyperplastic polyps were observed in seven patients, tubular adenoma in two, inflammatory polyps in one and hamartomatous polyps in one, respectively. All patients underwent comprehensive treatment and five achieved clinical remission. A total of 2107 DEGs, including 1265 upregulated and 842 downregulated, were found in the gastric polyp. Gene ontology analysis showed that upregulated genes were significantly enriched in the positive regulation of cell proliferation, epithelium development and angiogenesis. A protein–protein interaction analysis suggested that INHBA was at the center of the interaction network and might play an important role in CCS. Immunohistochemistry confirmed that INHBA expression was upregulated in CCS gastric polyps. Conclusions CCS is a rare disease and its diagnosis mainly depends on typical clinical manifestations, endoscopic findings and histological features. INHBA upregulation may contribute to its pathogenesis. Eight patients with Cronkhite–Canada syndrome (CCS) admitted to our hospital from January 2005 to November 2019 were retrospectively evaluated. Transcriptome profiling was performed in one patient to investigate its difference between gastric polyp tissue and normal mucosa. Differentially expressed genes (DEGs) were determined and used for functional analysis. Transcriptome profiling and further immunohistochemical verification suggest that inhibin beta A (INHBA) upregulation may contribute to CCS pathogenesis.